2016
DOI: 10.4338/aci-2015-10-ra-0129
|View full text |Cite
|
Sign up to set email alerts
|

Usability Testing of Two Ambulatory EHR Navigators

Abstract: SummaryBackground: Despite widespread electronic health record (EHR) adoption, poor EHR system usability continues to be a significant barrier to effective system use for end users. One key to addressing usability problems is to employ user testing and user-centered design. Objectives: To understand if redesigning an EHR-based navigation tool with clinician input improved user performance and satisfaction. Methods: A usability evaluation was conducted to compare two versions of a redesigned ambulatory navigato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…Similar to a study of another type of EHR functionality (i.e., ambulatory navigators), we observed that perceived cognitive load was unrelated to participant performance. 28 This study has several limitations that reduce its generalizability including its single organization, and relatively small sample size. Our convenience sample was limited to mid-level resident physicians which may affect generalizability.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to a study of another type of EHR functionality (i.e., ambulatory navigators), we observed that perceived cognitive load was unrelated to participant performance. 28 This study has several limitations that reduce its generalizability including its single organization, and relatively small sample size. Our convenience sample was limited to mid-level resident physicians which may affect generalizability.…”
Section: Discussionmentioning
confidence: 97%
“…Although the usability of electronic health records (EHRs) by physicians is well studied [45], little is known about the usability of electronic platforms to support dietitians’ use of patient data from apps. The Easy Diet Diary Connect platform has a comparative SUS score to evaluations of certain EHRs [46]. However, other literature has highlighted that physicians perceive EHRs to have poor usability amidst a range of other limitations relating to inefficiencies from improper integration and interference with face-to-face patient care [45].…”
Section: Discussionmentioning
confidence: 99%
“…17 One strategy to address these issues has focused on redesigning EHRs, with multiple studies examining how to improve EHR usability, optimize user interfaces, and reduce click burden. 8,[18][19][20][21][22][23] However, executing EHR design changes can be constrained by limitations imposed by institutional infrastructure or by EHR vendors. Another strategy to reduce the documentation burden and altered physician-patient communication patterns imposed by EHRs is to use scribes.…”
Section: Background and Significancementioning
confidence: 99%